2018
DOI: 10.1097/01.nep.0000000000000382
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Experiences of DNP-Prepared Nurses Enrolled in a DNP-to-PhD Pathway Program

Abstract: The advancement of the doctor of nursing practice (DNP) degree and the need for nurse researchers with a doctor of philosophy (PhD) has led to significant growth in doctoral nursing education. Some DNP graduates have chosen to pursue a second terminal degree. This descriptive study explored the experiences of students completing a DNP-to-PhD pathway program. Data analysis revealed that DNP-to-PhD students desired acceptance in academia. Implications suggest the need for additional pathway programs, clear commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Implementation research is focused on the study of the uptake of research findings into clinical practice to improve the quality and effectiveness of health services (Demiris, Oliver, Capurro, & Wittenberg-Lyles, 2014). The results from this review intimate that NP research into the outcomes of health-care transformation is more suited to this research methodology than the more tra- however, the research indicates that this is also proving insufficient in research preparation, as it is a practice-focused rather than research-focused educational preparation (Carlson, Staffileno, & Murphy, 2018;Sebach & Chunta, 2018). This review did not determine the education preparation of NPs in respect of the role in health-care transformation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Implementation research is focused on the study of the uptake of research findings into clinical practice to improve the quality and effectiveness of health services (Demiris, Oliver, Capurro, & Wittenberg-Lyles, 2014). The results from this review intimate that NP research into the outcomes of health-care transformation is more suited to this research methodology than the more tra- however, the research indicates that this is also proving insufficient in research preparation, as it is a practice-focused rather than research-focused educational preparation (Carlson, Staffileno, & Murphy, 2018;Sebach & Chunta, 2018). This review did not determine the education preparation of NPs in respect of the role in health-care transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Gallen et al (2019) confirmed this by identifying those frontline nurses, including master's degree‐prepared NPs, in Ireland perceived a lack of preparedness in the methods and tools required to undertake quality and safety improvement projects. Academic preparation for NPs in the United States is now at doctoral level; however, the research indicates that this is also proving insufficient in research preparation, as it is a practice‐focused rather than research‐focused educational preparation (Carlson, Staffileno, & Murphy, 2018; Sebach & Chunta, 2018). This review did not determine the education preparation of NPs in respect of the role in health‐care transformation.…”
Section: Discussionmentioning
confidence: 99%
“…As DNP and PhD graduates will likely serve as preceptors or have contact with students in an academic or clinical setting, doctoral nursing programs without a nurse educator focus should consider offering nurse educator courses as electives. Finally, DNP-to-PhD pathway programs (Sebach & Chunta, 2018), PhD-to-DNP pathway programs, and postgraduate certificate programs in nursing education are additional opportunities to enhance academic nurse educator skill acquisition.…”
Section: Discussionmentioning
confidence: 99%
“…High-achieving nursing students and practicing nurses desiring a doctoral degree must make a choice between the DNP and the PhD (Bednash et al, 2014). While a handful of researchers have described the barriers and facilitators to PhD and/or DNP pursuit (Dreifuerst et al, 2016;Lee et al, 2013;Loomis, Willard, & Cohen, 2006;Rocafort et al, 2020;Sebach & Chunta, 2018;Squires et al, 2014), their use of surveys and semi-structured interview questions, often with small, homogeneous samples, may have resulted in findings that are missing crucial information, leading to blind spots in our understanding of this phenomenon. Qualitative studies that employ unstructured interview questions and recruit a varied sample are needed to gain a richer understanding of PhD perceptions and decision-making regarding doctoral pursuit.…”
Section: Implications For Future Researchmentioning
confidence: 99%
“…For example, Xu et al (2018) found that students who entered the PhD directly from baccalaureate programs were committed to science and wanted to contribute to the scientific knowledge base in nursing. The perspectives of students in dual degree (DNP and PhD) and DNP-to-PhD programs also need to be explored, as enrollments in these programs are steadily growing and may present a unique opportunity to bolster the PhD-prepared nursing workforce (AACN, 2010;Greco, 2019;Loescher & Love, 2021;May et al, 2020;McNair Scholars Program;Sebach & Chunta, 2018).…”
Section: Implications For Future Researchmentioning
confidence: 99%